Analisis perilaku petani padi sawah terhadap kinerja penyuluh pertanian di Kecamatan Muara Bulian Kabupaten Batang Hari - Uliya Uliya; Reno Armando; Tukidi; Enita (Journal of Creative Attitudes Culture, 2026)
Analysis of the behavior of rice farmers towards the performance of agricultural extension workers in Muara Bulian District, Batang Hari Regency by: Uliya, Reno Armando, Tukidi, Enita. The purpose of this study was to determine the behavior of rice farmers towards the performance of agricultural extension workers in Muara Bulian District, Batang Hari Regency. The data analysis method used Multiple Linear Regression. The results of this study are The results of the t-test analysis show that: education factors (X2) land area (X3), significantly influence the performance of agricultural extension workers (Y). While education factors (X2), length of farming (X4), Access to information (X5) and member involvement in groups (X6).